Knowledge, Attitude and Behavior of Undergraduate Dental Students towards Cardiopulmonary Resuscitation: A Descriptive Study - Deesha Kumari1 , Thara Chandran2 , Bless Annie Philip3 , Mithun K4 , ShilpaM5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Context: Medical Emergencies can be encountered by any individual, and its occurrence is usually high in a Dental setting due to the procedures involved. Hence it is important that Dentists be equipped with the knowledge of Cardiopulmonary resuscitation (CPR). Aims: The Study aims to assess the Knowledge, Attitude and Behavior of Dental Undergraduate students towards CPR training. Methods and Materials: The present study was a Cross Sectional study conducted among 163 Final Year Undergraduate students and Interns of a Dental Institution in Mangalore. A validated Self Structured Questionnaire was distributed to the students. Statistical Analysis: Descriptive and Inferential statistics like Student’s Unpaired T Test determined the difference in Knowledge, Attitude and Behavior among the participants. Results: The overall Knowledge of Students regarding CPR was Poor, with Interns possessing a Significantly higher Knowledge than Final Year BDS Students. Amidst the poor Knowledge, 75.5% students were trained in CPR and 65.6% students were ready to perform CPR in an emergency situation thus displaying a Positive Attitude. Conclusion: The present study showed that despite a dearth in CPR Knowledge among the Students, they exhibited a Positive Attitude and Behavior towards Training and Practice of CPR. Thus the study highlights the need to strengthen CPR training among Dental Students, by Inculcating and Standardizing it in the Undergraduate and Postgraduate curriculum.